Advance in earthquake prediction by physical simulation on the baikal ice cover - Dobretsov N. L.; Ruzhich V. V.; Psakhie S. G. Sergey Grigorievich; Chernykh E. N.; Shilko E. V. Evgeny Viktorovich; Levina E. A.; Ponomareva E. I. (2013, 2013)
Title screen